THE RISK OF DISORDERED MUSCULOSKELETAL DISEASE IN WORKERS - Irwan irwan; Nur Ayini S Lalu; Ainun Ramadhanty Noe (Jambura Journal of Health Sciences and Research, 2021)
Musculoskeletal Disorders (MSDs) are disorders that affect the function of the musculoskeletal system due to repeated exposure. The purpose of this study was to determine the relationship between Manual Handling activity and work posture on the risk of Musculoskeletal Disordes in workers. This research uses quantitative research, analytical survey method with cross-sectional research approach. The sample in this study were 15 respondents, namely transport workers at UD. Barokah. The sampling technique in this research is purposive sampling. Analysis of research data using chi-square test analysis The results obtained that the variables that have a relationship with the risk of Musculoskeletal Disordes are Manual Handling Activities (Ï = 0.008), Work Posture (Ï = 0.045), the conclusion is that there is a relationship between Manual Handling Activities and Work Postures on Musculoskeletal Disordes in lifting and transport workers at UD .Barokah Suggestions for business owners to provide ergonomic work facilities